Composting of selected organic wastes from peri-urban areas of Harare, Zimbabwe - Mhindu, Rangarirayi L; Wuta, Menas; Ngorima, Esther (Springer, 2021)
Background The composting process of peri-urban household wastes, changes that occur during composting, and the properties of the composting products that are of importance for use as soil amendments were studied. Seven different composting mixtures were made in large piles consisting of fallen tree leaves and fresh vegetable leaves mixed with grass or maize straw (0%, 10%, 30% and 50% w/w), wastes common in peri-urban areas of Harare.